2016
DOI: 10.5194/nhess-16-1553-2016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic modelling of coastal seas: the role of tidal dynamics in the Messina Strait, Western Mediterranean Sea

Abstract: Abstract. This work explores the importance of considering tidal dynamics when modelling the general circulation in the Messina Strait, a narrow passage connecting the Tyrrhenian and the Ionian subbasins in the Western Mediterranean Sea. The tides and the induced water circulation in this Strait are among the most intense oceanographic processes in the Mediterranean Sea. The quantification of these effects can be particularly relevant for operational oceanographic systems aimed to provide short-term prediction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…This marked seasonality may be related to the homeothermy of the water column characterizing the Mediterranean winter and the study area (Cucco et al, 2016), which enables wider depth excursions for mesopelagic species. In the same way, during summer, the thermohaline features of the water column (Cucco et al, 2016) may represent an obstacle to diel vertical migration. Indeed, according to Paxton (1967), temperature is among the most import- Ishimaru, & Ohno, 1999;Gartner, Sulak, Ross, & Necaise, 2008;Sutton et al, 2008;Olivar et al 2012) have demonstrated that some lanternfish species have a non-migratory portion of the population, usually found in deeper layers, or have different diel vertical migration patterns, with younger fish migrating to the near surface at night to a greater extent than older individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This marked seasonality may be related to the homeothermy of the water column characterizing the Mediterranean winter and the study area (Cucco et al, 2016), which enables wider depth excursions for mesopelagic species. In the same way, during summer, the thermohaline features of the water column (Cucco et al, 2016) may represent an obstacle to diel vertical migration. Indeed, according to Paxton (1967), temperature is among the most import- Ishimaru, & Ohno, 1999;Gartner, Sulak, Ross, & Necaise, 2008;Sutton et al, 2008;Olivar et al 2012) have demonstrated that some lanternfish species have a non-migratory portion of the population, usually found in deeper layers, or have different diel vertical migration patterns, with younger fish migrating to the near surface at night to a greater extent than older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…During winter this phenomenon was accentuated, although species richness was slightly higher in spring, influenced by the presence of juveniles of several species. This marked seasonality may be related to the homeothermy of the water column characterizing the Mediterranean winter and the study area (Cucco et al., ), which enables wider depth excursions for mesopelagic species. In the same way, during summer, the thermohaline features of the water column (Cucco et al., ) may represent an obstacle to diel vertical migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study focused on the Euripus Strait, close to Chalkis, Greece, has examined the use of turbines that are suitable according to the space limitations of the area and it has been concluded that the potential amount of tidal-stream energy in this strait is insufficient for wide-scale applications [187]. On the contrary, the Strait of Messina is characterized by high-energy tidal currents with maximum velocities at spring peak tides ranging from 1.8 m/s to more than 3 m/s, proving the suitability of the site for tidal energy harnessing [188,189]. However, in [82], it has been suggested that resource feasibility studies should be based on annual average power density instead of mean spring peak tidal velocities because of the significant resource underestimation associated with the latter.…”
Section: Tidal/current Energymentioning
confidence: 99%
“…The model resolves, for each layer, the vertically integrated shallow water equations in their formulation with water levels and transport terms. It was applied with success to reproduce the main hydrodynamics in gulfs, harbors, lagoons and coastal seas (Cucco et al, 2012;Umgiesser et al, 2014;Ferrarin et al, 2014;Cucco et al, 2016a;Farina et al, 2018). The model uses finite elements for horizontal spatial discretizations, z-layers for vertical discretizations and a semi-implicit algorithm for integration in time.…”
mentioning
confidence: 99%